Evidence Based Clinical Study in Cases of Essential Hypertension in Response to Homoeopathic Treatment in LM Potency (Advancements in Homeopathic Research, 2022)
Background & Objectives: At the present day, an elevated blood pressure level is recognized as the most important public health problem in the developed countries and essential hypertension is held responsible for more than 95% of the cases. It is common, asymptomatic and leads to lethal complications if left untreated. The “silent killer” as it is known, is gradually becoming a problem of enormous proportions in the developing world also. Hypertension is the most important modifiable risk factor for coronary heart disease(CHD), stroke ,congestive heart failure, end stage renal disease and peripheral vascular disease. Methods: A total of seventy (70) well diagnosed cases of essential hypertension were registered for treatment at the Out Patient Department of R.V.S Homoeopathic medical college and hospital, Sulur, Coimbatore, Tamilnadu, between February 2017 and June 2018. Results & Interpretation: Out of 70 patients, 65 patients were cured, 03 patients did not improve and 02 patients dropped out. Proper case taking was done in each case and medicines prescribed on holistic basis. The outcome measure is the systolic and diastolic blood pressure values measured using sphygmomanometer after the period of the study. These were compared with the initial values, and the difference analyzed using statistical tests, to find the efficacy of the treatment. Conclusion: At the end of study, it was found that Homoeopathic medicines selected from synthesis repertory and administered in LM potency has proven its beneficial effect for patients suffering from Essential hypertension.
Keywords: essential hypertension; LM potency; Homoeopathy